A study of factors determining outcome of acute kidney injury patients requiring hemodialysis - G., Vasanth; P., Surendrakumar; P., Catherine; G., Venu (International Journal of Research in Medical Sciences, 2018)
Background: High mortality rate in acute kidney injury (AKI) has interested many authors to conduct studies about factors predicting its outcome. The need for both dialysis and ICU care defines a group of critically ill patients who may have poor prognosis and consume vast amounts of resources. In this study we determine the variables predicting the outcome of patients with severe acute kidney failure requiring haemodialysis and to ascertain the aetiology of acute kidney injury in this group. Methods: We prospectively analysed 114 patients admitted with severe renal failure requiring renal replacement therapy over a period of one year. The influence of various factors such as demographic variables, pre morbidities, details of admission, clinical presentation and extent of organ dysfunction on the clinical outcome such as mortality and progression to end stage kidney disease were statistically analyzed using SPSS version 12 (SPSS Inc., Chicago, Ill). Results: Univariate and multivariate analysis showed that parameters such as chronic liver disease, preexisting heart disease, mechanical ventilation and vasopressor requirement, oliguria, sepsis, hepatorenal syndrome, cardiogenic shock and admission in ICU were associated with high mortality (p<0.05). Of the 114 patients, 49 died (42.98%), 61 (53.5%) were dialysis independent and 4 patients (3.5%) progressed to end stage renal disease (ESRD). Conclusions: AKI patients requiring hemodialysis were associated with high hospital mortality. Patients who were diagnosed to have acute glomerulonephritis especially rapidly progressing glomerulonephritis as the cause of AKI were more prone to ESRD. Most survivors were dialysis independent at the time of discharge.